The Effect of Feed to Inoculums Ratio on Biogas Production Rate from Cattle Manure Using Rumen Fluid as Inoculums - S. Sunarso; Seno Johari; I Nyoman Widiasa; B. Budiyono (International Journal of Science and Engineering, 2010)
In this study, rumen fluid of animal ruminant was used as inoculums to increase biogas production rate from cattle manure at mesophilic condition. A series of laboratory experiments using 400 ml biodigester were performed in batch operation mode. Given 100 grams of fresh cattle manure was fed to each biodigester and mixed with rumen fluid and tap water resulting five different feed to inoculum (F/I) ratios (i.e. 17.64, 23.51, 35.27, and 70.54). The operating temperatures were varied at room temperature. The results showed that the rumen fluid inoculated to biodigester significantly effected the biogas production. Rumen fluid inoculums caused biogas production rate and efficiency increase more than two times in compare to manure substrate without rumen fluid inoculums. At four F/Is tested, after 80 days digestion, the biogas yield were 191, 162, 144 and 112 mL/g VS, respectively. About 80% of the biogas production was obtained during the first 40 days of digestion. The best performance of biogas production will be obtained if F/I ratio is in the range of 17.64 to 35.27 (correspond to 25 – 50 % of rumen fluid). The future work will be carried out to study the dynamics of biogas production if both the rumen fluid inoculums and manure are fed in the continuous system